Republic of Moldova : Poverty Reduction Strategy Paper Annual Evaluation Report 2005. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper reviews the Poverty Reduction Strategy Annual Evaluation Report 2005 for Moldova. Economic growth and income redistribution policies promoted in the context of Economic Growth and Poverty Reduction Strategy (EGPRS) implementation contributed to higher incomes and improved access of population to social services, which led to higher living standards and poverty reduction in Moldova. During 2002-04, poverty rates decreased by 14.5 percentage points. By 2004, only 26.5 percent of the population of Moldova was poor. The most essential decrease took place in 2002-03.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet